2001
DOI: 10.1097/00002030-200109280-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA decrease in subcutaneous adipose tissue of HIV-infected individuals with peripheral lipoatrophy

Abstract: Lipodystrophy with peripheral fat wasting following treatment with NRTI-containing HAART is associated with a decrease in subcutaneous adipose tissue mtDNA content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
2
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(140 citation statements)
references
References 16 publications
8
128
2
2
Order By: Relevance
“…Increased systemic lactate levels were previously reported in HIV patients undergoing HAART (52). Adipose tissue mitochondrial damage from HAART with subsequent increased lactate production was hypothesized as the most likely cause of hyperlactatemia in these patients (12,45,63,67), as liver lactate clearance was found to be normal (58). Our results suggest that adipose tissue is indeed one possible source of the increased circulating lactate, but this does not preclude increased lactate production from other tissues such as muscle.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Increased systemic lactate levels were previously reported in HIV patients undergoing HAART (52). Adipose tissue mitochondrial damage from HAART with subsequent increased lactate production was hypothesized as the most likely cause of hyperlactatemia in these patients (12,45,63,67), as liver lactate clearance was found to be normal (58). Our results suggest that adipose tissue is indeed one possible source of the increased circulating lactate, but this does not preclude increased lactate production from other tissues such as muscle.…”
Section: Discussionmentioning
confidence: 59%
“…PI have been reported to induce insulin resistance, to decrease glucose transport and adipogenesis (8,48,49,57,60,70), to either increase (51) or decrease preadipocyte differentiation in 3T3-L1 adipocyte cell lines (8,14), and to increase apoptosis in human subcutaneous adipose tissue (13). In addition, NRTI have been shown to have a toxic effect on mitochondrial DNA in human subcutaneous adipose tissue (45,63,67).…”
mentioning
confidence: 99%
“…Lipoatrophy has been associated with decreases in mtDNA in subcutaneous fat [45]. The duration of NRTI use and the use of NRTIs with strong inhibition of mtDNA are the most important risk factors for development of lipoatrophy.…”
Section: Lipoatrophymentioning
confidence: 99%
“…For example, it has been shown the HAART drug combination of zidovudine (AZT) and the PI, indinavir (IDV) can disrupt the function and viability of endothelial cells due to loss of mitochondrial membrane potential; partially reversible with the thiol antioxidant N-acetylcysteine amide [32]. In adipocytes from HAART treated patients, it has also been shown that NRTI administration correlated positively with mitochondrial DNA depletion [41,42] suggesting an etiology for the lipodystrophy imparted by HAART. There are also coherent experimental and clinical arguments for the existence of mitochondrial toxicity following perinatal exposure to AZT, alone or in combination with the NRTI 3TC [43,44].…”
Section: Disruption Of Mitochondrial Function By Haartmentioning
confidence: 99%